Coyote's mate - Leigh, Lora (Leigh, Lora. Novel of the Breeds., 2009)
Despite the fact that Del-Rey Delgado, the genetically altered rebel known as the Coyote Ghost, betrayed her during a rescue mission, Anya Korbin, an altered Coyote breed, is unable to deny the animalistic desire between them.